GAMBARAN KECERDASAN EMOSIONAL PADA WANITA DEWASA AWAL DENGAN LATAR BELAKANG FATHERLESS - Kintan Aulia Rahmat; Roswiyani Roswiyani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the emotional intelligence profile of young adult women who grew up without a father. This study uses a qualitative method with a phenomenological approach to gain an in-depth understanding of the emotional experiences of the participants. There were ten participants, all young adult women who grew up without a father. Data collection was conducted through observation and semi-structured interviews. Data analysis used the stages of data reduction, data presentation, and conclusion drawing. The results showed that the participants' emotional intelligence was still developing and was greatly influenced by their life experiences without a father. An unstable childhood also contributed to different emotional adaptations in each participant. The participants' emotional intelligence showed positive development, but had not yet reached the ideal level. This fatherless condition presented emotional challenges that shaped the participants' adaptive abilities in early adulthood.